Delay constraint multipath routing for wireless multimedia ad hoc networks. (12th May 2014) - Sun, Yanjing; Sun, Jianguang; Zhao, Fangfang; Hu, Zhuoxian
Summary: According to the disadvantages of real time and continuity for multimedia services in ad hoc networks, a delay constraint multipath routing protocol for wireless multimedia ad hoc networks, which can satisfy quality of service (QoS) requirement (QoS multipath optimized link state routing [MOLSR]), is proposed. The protocol firstly detects and analyzes the link delay among the nodes and collects the delay information as the routing metric by HELLO message and topology control message. Then, through using the improved multipath Dijkstra algorithm for path selection, the protocol can gain the minimum delay path from the source node to the other nodes. Finally, when the route is launched, several node‐disjoint or link‐disjoint multipaths will be built through the route computation. The simulation and test results show that QoS‐MOLSR is suitable for large and dense networks with heavy traffic. It can improve the real time and reliability for multimedia transmission in wireless multimedia ad hoc networks. The average end‐to‐end delay of QoS‐MOLSR is four times less than the optimized link state routing. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this paper, a new architecture of improved Dijkstra algorithm based on the metric of delay constraint is presented to perform minimum delay multipath selection by making use of greedy algorithm. We use the multipath optimized link state routing (MOLSR) protocol to implement the M‐Dijkstra algorithm. Through the process of topology discovery and route computation, the improved protocol (QoS‐MOLSR) can gain the minimum delay multipath route, which is proved to be suitable for multimedia transmission in wireless multimedia ad hoc networks.